Pengaruh Kepemimpinan Transformasional, Komunikasi Dan Pelatihan Terhadap Kinerja Karyawan Pada PT Kimia Farma Apotek Unit Bisnis Denpasar - I Kadek Angga Wiguna; Anak Agung Dwi Widyani; Putu Ayu Sintya Saraswati (UNHI Press, 2023)
Good employee performance is a step towards achieving organizational goals, so it is necessary to make efforts to improve employee performance. The purpose of this study was to determine the effect of transformational leadership, communication, and training on employee performance. This research was conducted at the business unit of PT Kimia Farma Apotek Denpasar. The sample for this research is 72 employees of PT. Kimia Farma Denpasar Pharmacy Business Unit. The method used to determine the sample in this study is the saturated sample method. Data collection was carried out through documentation, interviews, and questionnaires. The data analysis technique used in this research is linear regression analysis with the SPSS version 23 program. This shows a positive influence on Transformational Leadership, Communication, and Training which is significant for the performance of PT. Kimia Farma Denpasar Pharmacy Business Unit so that Hypothesis 1 (one), Hypothesis 2 (two), and Hypothesis 3 (three) are accepted.